ChatGPT in Learning: The Case Study of Motives and Implications for Islamic School Educators in Indonesia - Jaya Jaya; Adi Pratama Awadin; Muhammad Jusuf Nur Ikhsan; Mira Zuzana (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2025)
The development of Artificial Intelligence (AI) technology has seen significant progress and has become an attractive platform for improving the quality of education. In recent years, interest in AI-based applications has been very high among academics, including Islamic school educators in Indonesia. This paper aims to highlight the motives and implications of Islamic school educators in using ChatGPT in learning. This article uses qualitative research with a field research design. Primary data sources are derived from interviews, where the main data were obtained through interviews with Islamic school educators at the Madrasah Aliyah (MA) and Madrasah Tsanawiyah (MTs) levels in Indonesia. Secondary data were obtained from scientific articles (journals), books, websites, and other relevant literature related to the research object. Data collection techniques included interviews and documentation. Data analysis techniques were based on Miles et al., namely data condensation, data presentation, and conclusion drawing. The results of this study indicate that ChatGPT offers numerous benefits for educators, including enhancing and facilitating access to information, searching for teaching materials, and accessing learning resources. However, despite its many advantages, the use of ChatGPT in education also presents several challenges, such as dependence on technology, potential ethical violations, and privacy concerns. These negative impacts, if not addressed, could have adverse effects on educators in schools.